Development of Video-Based Teaching Materials Assisted by the Sparkoll Videoscribe Application in Mathematics Learning for Grade VIII SMP N 5 Bilah Barat - Nurliani Manurung; Sarah Br Sirait (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to validate the video-based teaching materials that have been developed. Three material experts and three media experts conducted a feasibility test of video-based teaching materials using cube and block building materials, using pre and post tests to determine the effectiveness of the material. this instructional video and student answers. The subjects in this study were 31 class VIII students of SMP N 5 Bilah Barat. This study uses the ADDIE approach for development research (R&D). The research instruments included material and media expert validation sheets, pretest and posttest questions, and student answer surveys. These results obtained data validation from material experts 81.66% (Very Eligible), media experts 86.11% (Very Eligible), an increase in pretest-posttest results 0.51% in the medium category, and student responses accounted for 88.06% of total (Strongly agree). The results of the validation of video-based teaching materials assisted by Sparkol Videoscribe for learning mathematics show that teaching materials are very suitable for use as teaching materials in learning mathematics.